Dishevelled enables casein kinase 1-mediated phosphorylation of Frizzled 6 required for cell membrane localization - Strakova, Katerina; Kowalski-Jahn, Maria; Gybel, Tomas; Valnohova, Jana; Dhople, Vishnu M; Harnos, Jakub; Bernatik, Ondrej; Ganji, Ranjani Sri; Zdrahal, Zbynek; Mulder, Jan; Lindskog, Cecilia; Bryja, Vitezslav; et al. (The Journal of biological chemistry, 2018)
Frizzleds (FZDs) are receptors for secreted lipoglycoproteins of the Wingless/Int-1 (WNT) family, initiating an important signal transduction network in multicellular organisms. FZDs are G protein-coupled receptors (GPCRs), which are well known to be regulated by phosphorylation, leading to specific downstream signaling or receptor desensitization. The role and underlying mechanisms of FZD phosphorylation remain largely unexplored. Here, we investigated the phosphorylation of human FZD6 Using MS analysis and a phospho-state- and -site-specific antibody, we found that Ser-648, located in the FZD6 C terminus, is efficiently phosphorylated by casein kinase 1 ϵ (CK1ϵ) and that this phosphorylation requires the scaffolding protein Dishevelled (DVL). In an overexpression system, DVL1, -2, and -3 promoted CK1ϵ-mediated FZD6 phosphorylation on Ser-648. This DVL activity required an intact DEP domain and FZD-mediated recruitment of this domain to the cell membrane. Substitution of the CK1ϵ-targeted phosphomotif reduced FZD6 surface expression, suggesting that Ser-648 phosphorylation controls membrane trafficking of FZD6 Phospho-Ser-648 FZD6 immunoreactivity in human fallopian tube epithelium was predominantly apical, associated with cilia in a subset of epithelial cells, compared with the total FZD6 protein expression, suggesting that FZD6 phosphorylation contributes to asymmetric localization of receptor function within the cell and to epithelial polarity. Given the key role of FZD6 in planar cell polarity, our results raise the possibility that asymmetric phosphorylation of FZD6 rather than asymmetric protein distribution accounts for polarized receptor signaling.
Keywords: frizzled receptory; protilátky; cell signaling; GRK; Epithelium; epitel; HEK293 buňky; casein kinase 1; fosforylace; receptor regulation; protein dishevelled; signální transdukce; Phosphorylation; Amino Acid Sequence; HEK293 Cells; fosfoproteiny; Mass Spectrometry; Dishevelled; Phosphoproteins; Dishevelled Proteins; kaseinkinasa I; Signal Transduction; scaffold protein; Frizzled Receptors; Cell Membrane; G protein-coupled receptor (GPCR); Antibodies; WNT; phosphorylation; lidé; ženské pohlaví; Humans; Fallopian Tubes; buněčná membrána; vejcovody; sekvence aminokyselin; Frizzled; hmotnostní spektrometrie; cell polarity; Casein Kinase I; Female; Serine; serine/threonine protein kinase; serin